Bimbingan IT Fundamental Video Pembelajaran untuk Tenaga Guru di SDN Inpres 133 Pari’risi Kabupaten Takalar - Faradibah, Amaliah; Widyawati, Dewi; Belluano, Poetri Lestari Lokapitasari; Tenripada, A. Ulfah; Utami, Aulia Putri; Fatahillah, Furqon; A.R Tuasamu, Fatimah (Universitas Dinamika, 2025)
The use of Information Technology has penetrated various sectors, including education. In the digital era, video editing applications are among the most widely used tools, as students tend to be more engaged with video-based content than with text-based learning materials. This study aims to improve teaching methods by empowering teachers to create engaging learning videos using digital applications. The program was implemented at SDN 133 Inpres Paririsi Takalar, involving 27 elementary school teachers with diverse educational backgrounds, teaching subjects, and teaching experience. A Practical and Participatory training model was applied over a two-month period. Evaluations were conducted before and after the training to assess its effectiveness in enhancing teachers’ video editing skills. The results showed a significant improvement in teachers' abilities to use video editing applications and increased confidence in delivering digital-based learning content. The main challenges faced by teachers included limited initial digital literacy and time constraints during implementation. This study contributes to addressing the digital content creation skill gap among elementary school teachers. The expected outputs include: (1) a user guide module for video editing applications, (2) publication in an accredited national journal, and (3) enrichment materials for the Multimedia Systems course. Further research is recommended to explore the long-term impact of the training and its applicability to other educational levels.